2006
DOI: 10.1097/01.sla.0000197561.70972.73
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Parenteral Tranexamic Acid in Liver Tumor Resection

Abstract: Perioperative parenteral use of TA reduced the amount of operative blood loss and the need for blood transfusion in elective liver tumor resection. A real "blood transfusion"-free hepatectomy may be feasible with the assistance of parenteral TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(30 citation statements)
references
References 39 publications
(196 reference statements)
0
30
0
Order By: Relevance
“…The incidence of significant bleeding in patients included in this study was lower than that for recent series in the literature. 13,1921 Lesions adjacent to or invading large hepatic veins are recognized to be at increased risk of bleeding. 22 The major risk factors for significant or uncontrolled bleeding are the size and location of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of significant bleeding in patients included in this study was lower than that for recent series in the literature. 13,1921 Lesions adjacent to or invading large hepatic veins are recognized to be at increased risk of bleeding. 22 The major risk factors for significant or uncontrolled bleeding are the size and location of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a randomised controlled trial investigating the effectiveness of tranexamic acid in hepatectomy patients, Wu et al reported that patients in the tranexamic acid group experienced significantly lower overall levels of perioperative blood loss when compared with a placebo group (300 mL versus 600 mL, p < 0.001). 25 Blood transfusion is another strategy which can be used to address anaemia during the perioperative period. However, this approach should be carefully considered as large cohort studies have reported a 29-32% higher risk of PM in surgical patients who receive perioperative transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…So some authors propose the utilization of drugs with antifibrinolytic effect like Aprotinin that is reported to be capable of reducing intraoperative blood loss (especially during liver resection time) and transfusions [117–119]. Other authors propose utilization of the cheaper Tranexamic acid reporting similar results [120]. Although a theoretical risk of thromboembolic complications is present, no adverse drug effects like deep venous thrombosis, pulmonary embolism, or other circulatory disturbances were detected in both these studies.…”
Section: How Can We Reduce Bleeding In Liver Surgery?mentioning
confidence: 99%